Petrogenesis of high heat producing granites and their contribution to geothermal resource in the Huangshadong geothermal field, South China - Liao, Yuzhong; Wang, Guiling; Xi, Yufei; Gan, Haonan; Yan, Xiaoxue; Yu, Mingxiao; Zhang, Wei; Zhao, Zirui (Frontiers in Earth Science, 2024)
The Huangshadong geothermal field (HGF), situated in the contact zone between Mesozoic granites and NE-striking dominant faults in South China, has great geothermal potential. Petrogenesis of reservoir rock plays an important role in understandings its genetic mechanism and assessing geothermal potential. However, due to the lack of rock sample at depth collected from the geothermal reservoir, the petrogenesis of granites in the geothermal reservoirs of the HGF, remains an enigma. This study elucidated the petrogenetic characteristics of these granites sampled directly from geothermal reservoir at the depth of ~3000 km and their geothermal implications through zircon U-Pb dating, geochemical analysis, and Hf isotopic analysis. The zircon U-Pb ages indicate that the magmatism evolution of HGF contains three eras, namely Cretaceous (135±4 to 143.6±2.8 Ma), Jurassic (152.7±2.7 to 176.7±1.8 Ma), and Permian granites (251±9.1 to 251±5 Ma) from the youngest to oldest. The reservoir granites were emplaced during the latest stage of Cretaceous intrusion, as indicated by the zircon U-Pb ages (135±4 Ma and 135.3±2.4 Ma) of rock samples from the deep part of well HR-1. These Cretaceous rocks are highly fractionated I-type granites, featuring high SiO2, K2O, and Na2O contents, high Rb/Sr ratios, low Zr/Hf, Nb/Ta, and Th/U ratios, and A/CNK values of 1.05-1.13. Compared to other Cretaceous granites outcropping on the margin of the HGF, these granites have undergone the strongest fractional differentiation. The Cretaceous granites in the HGF are high-heat-producing rocks (> 5 μW/m 3 ), with an average heat production rate of 6.63 μW/m 3 . Notably, the Cretaceous reservoir granites (as reservoir rocks) serve as an important heat source for the formation of geothermal resources in the HGF. In addition, the zircon Hf isotopic composition indicates that the reservoir Cretaceous granites originated from Meso-to Paleo-Proterozoic lower crustal materials (TDM2: 1385 to 1907 Ma).